Monoethylene Glycol Distillation System Design Validation, Operation and Effluent Treatment - Zaboon, Sami Mohammed Zaboon (Curtin University, 2019)
The sponsored bench-top scale Monoethylene glycol distillation unit located at Curtin University was designed and operated to use realistic production fluids, such as condensate mixtures and formation water/brines to simulate conditions representative industrial MEG systems. Many parameters such as MEG inlet concentration, temperature, rebiler temperature, inlet mass flowrate and reflux ratio have been experimentally examined to achieve the optimum conditions for the distillation process. These results were then compared with the results from HYSYS simulation.